Incidence, Clinical Characteristics, and Genotype Distribution of Rotavirus in a Neonatal Intensive Care Unit 5 Years After Introducing Rotavirus Vaccine - Yoon, Hye Sun; Lim, Jiseun; Sohn, Yong-Hak; Kim, Seung Yeon (Frontiers in Pediatrics, 2022)
Background: Rotavirus (RV) is a common cause of viral gastroenteritis in children worldwide. We aimed to investigate the incidence, symptoms, and genotype of RV infection in a neonatal intensive care unit (NICU) in South Korea five years after the introduction of RV vaccination to evaluate its effect on newborn infants. Methods: A total of 431 fecal specimens were collected from patients admitted to NICU between April 20, 2012, and September 10, 2013. Enzyme-linked immunoassays were used to detect RV antigen. Nested multiplex polymerase chain reaction was used for genotyping. Results: The overall incidence of RV infection was 43.9% and was significantly higher in preterm infants, infants born in the study hospital, low birth weight infants, and cesarean births (P < 0.05). Symptoms of vomiting, diarrhea, poor feeding, abdominal distension, and apnea were significantly higher in infants with RV infection than those without infection. RV infection gradually increased depending on infant care at home, postpartum clinic, or hospital (26.0%, 45.1%, and 60.2%, respectively; P = 0.000). The dominant RV genotype in the NICU was G4P[6] at 95%. Conclusion: Current RV vaccines did not affect the incidence of RV infection in newborn and preterm infants in the NICU. Most RV-positive patients in the NICU had symptoms, and the incidence of RV infection was relatively higher in hospitals and postpartum clinics with group life than home. The dominant RV genotype was G4P[6] across study groups.